Pattern and Risk Assessment of Bedsore in Hospitalized Patients - Ruhul Amin, Md; Monoarul Haque, Md; Saha, Pradip Kumar; Eusuf Zai, Sumaiya Zabin; Mahmud Hossain, Sarder; Akter, Sanjida (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Objective: This descriptive type of cross sectional study was conducted to assess pattern and risk factors of bedsore in hospital admitted patients in Dhaka city with a sample size of 114. Methods: A pretested, modified, questionnaire was used to collect the data. All the data were entered and analyzed by using Statistical Package of Social Science 16.0 versions. Results: Study found that 17.5%, 41.2%, 27.2% and 14% of the respondents belonged to age group of 1-20 years, 21-40 years, 41-60 years and 61-80 years respectively with mean age 37.97 +16.909 years. Responsible diseases for bedsore were spinal cord injury (41.2%), fracture (30%), stroke (24%), unconsciousness (7.2%) and GBS (2.8%) respectively. Study revealed that common area of bedsore were back of the sacrum (57%), back of the scapula (34.2%), medial aspect of knee joint (22.8%), malleoli (21.1%), greater trochanter of femur (15.8%), external occipital protuberance (14%), olecranon process of ulna (9.6%), above the coccyx (9.6%), iliac crest (7%), spine of the scapula (3.5%), posterior superior iliac joint (2.6%) and sacro-iliac joint (1.8%) respectively. Study also found that superficial and deep type of bedsore were 58.8% and 41.2% consecutively. Besides study revealed that 26.3% of the respondents were diabetic, 31.6% obese, 28.1% suffering from malnutrition, 61.4% did not use pneumatic bed and 7.2% patients did not maintain proper positioning 2 hourly and these were the risk factors of this study. Significant association was found between type of bed sore and use of pneumatic bed (P=0.000<0.05) as well as nutritional status (P=0.004<0.05). Conclusions: Changing position and use of pneumatic bed was best methods of prevention of bedsore. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21049